(untitled) (International Journal of Engineering and Computer Science, 2015)
High traffic volume and high traffic load exert a major impacts on roadways .The traffic volume is increasing continuously with passage of time and modern era. This increase in volume cause adverse impacts on roadways and highways and this increase in volume demands a good construction of roadways and means of transportation but during the last few decade, the continuously increasing in traffic volume and poor construction of roadways and highways in combination with an inappropriate due to Govt Policies and regulations cause an continuous deterioration of road network in Pakistan. As the traffic volume increases which cause the increase in traffic load and poor quality of construction or any compromise on the construction quality are the main cause on pavement failure especially in the fatigue cracking. In this research to improve the asphalt binder properties LDPE (Plastics) and crumb rubber are used .The proportion of Additives is kept 0.2% and 0.4% by the weight of bitumen content. In this study the different asphalt mixture are tested for resistance to creep by subjecting all specimen to UTM- 5P at the control load rate. Improvement in resistance against permanent deformation is monitored in Plastic modified bitumen and then crumbed rubber modified mix.